Educational Values in Surah as-Shaff 10-11 as an Instrument for Religious Character Formation - Alkausar Saragih; Nelvitia Purba (International Journal Ihya' 'Ulum al-Din, 2024)
Character values are traits or things that are considered important and useful in human life. Character values can also be used as instructions or guidelines for behavior. Character values can be formed and developed through education. Therefore, everyone, especially UMN Al-Washliyah students, must possess the importance of character education values through Islamic Education. This research aims to describe the values of Islamic education in Surah ash-Shaff verses 10-11, which means jihad, in forming the religious character of UMN Al-Washliyah students. By studying the values of Islamic education, it is hoped that it can shape students' character for the better. Islamic Education values will be formed by translating Surah Ash-Shaff verses 10-11 to form character education, especially for UMN Al-Washliyah students. The research method used is qualitative research with descriptive analysis. The results of this research are 1) Character education values for primary and secondary school students, namely the values or character that have been exemplified by the founders of Al-Washliyah who are strong and steadfast in practicing their religion or the values contained therein: Religious, honest, tolerant, Discipline, Hard Work, Creative, Independent, Democratic, Curiosity, National Spirit, Love of the Motherland, Respect for Achievement, Friendly/Communicative, Love of Peace, Love of Reading, Care for the Environment, Care for Social Responsibility. 2) Strategies for instilling character-building values for students, namely Incorporating character education into all courses on campus, Creating slogans or chants that can foster the habit of all students to behave well, and Getting used to good behavior. Positive attitude among campuses, and carrying out regular monitoring, giving rewards to students who always have good character.